NETWORKING 2011 10th International IFIP TC 6 Networking Conference, Valencia, Spain, May 9-13, 2011, Proceedings, Part II - Domingo-Pascual, Jordi; Manzoni, Pietro; Palazzo, Sergio; Pont, Ana.; Scoglio, Caterina; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The two-volume set LNCS 6640 and 6641 constitutes the refereed proceedings of the 10th International IFIP TC 6 Networking Conference held in Valencia, Spain, in May 2011. The 64 revised full papers presented were carefully reviewed and selected from a total of 294 submissions. The papers feature innovative research in the areas of applications and services, next generation Internet, wireless and sensor networks, and network science. The second volume includes 28 papers organized in topical sections on peer-to-peer, pricing, resource allocation, resource allocation radio, resource allocation wireless, social networks, and TCP.
Keywords: Computer science; Computer Communication Networks; Software engineering; Data encryption (Computer science).; Computer software; Information systems; Information Systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl.Internet).; Algorithm Analysis and Problem Complexity; Software Engineering; Management of Computing and Information Systems; Data Encryption